Introduction to the importance of learning English for early childhood and elementary schools age children in Jampang Village, Bogor - Syahadah Albaqiyatul Karimah; Widya Rahmawati Al-Nur (Universitas Muhammadiyah Magelang, 2023)
This community service activity was motivated by the lack of understanding of early childhood and elementary school age children in Jampang village, Bogor regarded the importance of English competencies. In addition, curriculum changes from 2013 curriculum in which the English was not taught in elementary towards the independent curriculum in which English is subject that starting from elementary. The aim of this activity is to prepare the children as the students to face the independent curriculum by providing an understanding of the importance of English and increasing the basic vocabulary skills. The three stages of implementing this activity are socialization, demonstration or practice about basic vocabulary, and evaluation. The results showed enlargement understanding of the English learning and the participants' ability to master basic English vocabulary.